A training module to empower marginalised Northern Borneo islanders for tuberculosis control - Jeffree, Mohammad Saffree (J Public Health Res, 2020)
Empowering marginalised urban islanders with limited health accessibility through knowledge transfer program for controlling pulmonary tuberculosis (PTB) requires a specific training module. The study was aimed to develop this training module by adapting and modifying the IMCI (Integrated Management of Childhood Illness) framework. Structuring the content for the knowledge and skills for PTB control in the module was based on the National Strategic Plan for Tuberculosis Control 2016-2020. A total of five knowledge and skills were structured: i) PTB disease and diagnosis, ii) PTB treatment, iii) preventive PTB measures, iv) prevention of malnutrition, and v) psychosocial discrimination. The IMCI framework was modified through 3 ways: i) identifying signs and symptoms of PTB, ii) emphasising the IMCI’s 5 steps of integrated management: assess, diagnose, treat, counsel and detect, and iii) counseling on BCG immunisation, malnutrition, environmental modifications and stigma on PTB.